Medicinal plants sold for treatment of bacterial and parasitic diseases in humans in Maputo city markets, Mozambique - Filomena Barbosa; Delfina Hlashwayo; Victor Sevastyanov; Valeriano Chichava; Adilência Mataveia; Ernesto Boane; Aida Cala (BMC, 2020)
Abstract Background In Mozambique, bacterial and parasitic diseases contribute to a high burden of mortality and morbidity. These infectious diseases are treated with antibiotics, antihelmintic or antiparasitic drugs. However, misuse of these has been affecting the potential to treat ailments. It has been reported that many people from Maputo city and province apart from the existing contemporary medicine, still use medicinal plants for treatment of diseases due to traditional heritage and beliefs. It is, therefore, important to register this knowledge in order to use it for future pharmacological studies. This study aimed to identify the medicinal plants sold in Xipamanine, Xiquelene and Mazambane markets for treatment of bacterial and parasitic diseases. Methods An ethnobotanical survey, using interviews, was conducted to the main vendors of the markets. Data about the plant name, part used, mode of preparation and administration route were collected. Results A total of 64 medicinal plants belonging to 32 families were listed as sold for treatment of bacterial and parasitic diseases in the three markets. Terminalia sericea, Elephantorrhiza elephantina, Tiliacora funifera and Hypoxis hemerocallidea were the most cited plants. Roots were the most often sold suggesting it is the most used part. We also found out that medicinal plants trade is still common in Maputo markets. This suggests that people still use plant-based herbal medicines for their basic health care. Conclusions Several medicinal plants were sold in Maputo city's markets for treatment of bacterial and parasitic diseases, with more emphasis on diarrhea and helminthiases. These plants were commonly bought by local residents and play an important role in the subsistence of vendors. Pharmacological studies are needed in order to isolate the plants active principles and understand their mechanism of action, so that new drugs can be developed.